Duration dependence and change-points in the likelihood of credit booms ending - Castro, Vítor (2013)
Whether the likelihood of credit booms ending is dependent on its age or not, or whether the respective behaviour is smooth or bumpy are important issues to which the economic literature has not given attention yet. This paper tries to fill that gap in the literature, exploring those issues with a proper duration analysis. Credit booms are identified considering two criteria well established in the literature: (i) the Mendoza-Terrones criteria; (ii) and the Gourinchas-Valdes-Landarretche criteria. A continuous-time Weibull duration model is employed over a group of 71 countries for the period 1975q1-2010q4 to investigate whether credit booms are duration dependent or not. Our findings show that the likelihood of credit booms ending increases over its duration and that these events have become longer over the last decades. Additionally, we extend the baseline Weibull duration model in order to allow for change-points in the duration dependence parameter. The empirical findings support the presence of a change-point: increasing positive duration dependence is observed in booms that last less than eight to ten quarters, but it becomes decreasing or even irrelevant for longer events. Analogous results are found for those credit boom episodes that are followed by systemic banking crisis (bad credit booms). Our findings also show that credit booms are, on average, longer in Industrial than in Developing countries.